Cohort profile: Impact of Maternal and Paternal Mental Health – Assessing Concurrent Depression, Anxiety and Comorbidity in the Canadian Family (IMPACT study). Issue 3 (8th March 2023) - Dennis, Cindy-Lee; Vigod, Simone; Grigoriadis, Sophie; Brown, Hillary; Brennenstuhl, Sarah; Dol, Justine; Wade, Mark; Falah-Hassani, Kobra; Shiri, Rahman; Marini, Flavia
Abstract : Purpose: This paper describes a prospective cohort, Impact of Maternal and Paternal Mental Health: Assessing Concurrent Depression, Anxiety and Comorbidity in The Canadian Family (IMPACT) study, which followed maternal–paternal dyads and their children across the first 2 years post partum. Participants: A total of 3217 cohabitating maternal–paternal dyads were recruited into the study from 2014 to 2018. Each dyad member separately completed online questionnaires at baseline (<3 weeks post partum) and again at 3, 6, 9, 12, 18 and 24 months on a variety of measures, including mental health, parenting environment, family functioning and child health and development. Findings to date: At baseline, the mean maternal age was 31.9±4.2 years and 33.8±5.0 years for fathers. Overall, 12.8% of families had a household income below the poverty line of $C50 000, and 1 in 5 mothers and 1 in 4 fathers were not born in Canada. One in 10 women experienced depressive symptoms during pregnancy (9.7%) and 1 in 6 had markedly anxious symptoms (15.4%) while 1 in 20 men reported feeling depression during their partner's pregnancy and 1 in 10 had marked anxiety (10.1%). Approximately 91% of mothers and 82% of fathers completed the 12-month questionnaire as did 88% of mothers and 78% of fathers at 24 months postpartum. Future plans: The IMPACT study will examine the influence of parental mental illness in the first 2 years of a child's life with a focus on understanding the mechanisms by which single (maternal or paternal) versus dual (maternal and paternal) parental depression, anxiety and comorbidity symptoms affect family and infant outcomes. Future analyses planned to address the research objectives of IMPACT will consider the longitudinal design and dyadic interparental relationship.